Energetyka obywatelska jako nowy etap rozwoju prawa energetycznego - Lissoń, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The subject of the article is the legal distinction of community energy as a new energy subsector. The creation of appropriate conditions for its development is to contribute to the achievement of EU and national goals related to the energy transformation. This study explains the concept of community energy, shows its goals, organizational forms, objects of activity, legal independence from traditional energy enterprises, and the place of regulations concerning this field of energy in the energy law system.
Keywords: community energy; local energy; distributed energy; energy law; state energy policy; renewable energy sources; citizen energy community; renewable energy prosumer; energy cooperative; energy cluster